Superfluid helium-4 in porous structures of neon-nitrogen nanoclusters as a target for low-mass dark matter detector - Boltnev, R. E.; Khmelenko, V. V. (Frontiers in Detector Science and Technology, 2025)
A new concept of three-phase projection chamber filled with a collection of neon-nitrogen nanoclusters immersed in superfluid helium-4 is proposed for detection light dark matter particles with low masses (0.1–10 Gev/c2). Such a time projection chamber includes a drift region within aerogel-like structure formed by neon-nitrogen nanoclusters filled by superfluid helium and a gas phase camera where electroluminescence takes place. The proposed concept combines the promising properties of liquid helium as a target material for direct detection of light dark matter particles such as high quenching factor, substantial scintillation light, high radiopurity, and high impedance to external vibration noise with the new ones determined by the properties of solid neon and nitrogen. The presence of highly porous impurity structure will enhance the primary scintillation signal (S1) due to light emission stimulated by interactions of metastable He2 (a3Σu) molecules and He+ ions with impurity nanoclusters. The signal of electrons produced by the recoil event (S2) and drifting in external electric field will get additional input due to energy stored in nitrogen atoms stabilized on the nanoclusters’ surface.